Biomarkers of male hypogonadism in childhood and adolescence - Rey, Rodolfo Alberto (2020)
Objectives: The objective of this review was to characterize the use of biomarkers of male hypogonadism in childhood and adolescence. Contents: The hypothalamic-pituitary-gonadal (HPG) axis is active during fetal life and over the first months of postnatal life. The pituitary gland secretes follicle stimulating hormone (FSH) and luteinizing hormone (LH), whereas the testes induce Leydig cells to produce testosterone and insulin-like factor 3 (INSL), and drive Sertoli cells to secrete anti-Müllerian hormone (AMH) and inhibin B. During childhood, serum levels of gonadotropins, testosterone and insulin-like 3 (INSL3) decline to undetectable levels, whereas levels of AMH and inhibin B remain high. During puberty, the production of gonadotropins, testosterone, and INSL3 is reactivated, inhibin B increases, and AMH decreases as a sign of Sertoli cell maturation. Summary and outlook: Based on our knowledge of the developmental physiology of theHPG axis, these biomarkers can be used in clinical practice to interpret the physiopathology of hypogonadism. Additionally, these markers can have diagnostic value in different forms of hypogonadism that may appear during childhood and adolescence.